2023
DOI: 10.1063/5.0146305
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion growth mechanism of penta-twinned Ag nanocrystals from decahedral seeds

Abstract: Crystals with penta-twinned structures can be produced from diverse fcc metals, but the mechanisms that control the final product shapes are still not well understood. By using the theory of absorbing Markov chains to account for the growth of penta-twinned decahedral seeds via atom deposition and surface diffusion, we predicted the formation of various types of products: decahedra, nanorods, and nanowires. We showed that the type of product depends on the morphology of the seed and that small differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Nevertheless, small nanocrystal seeds grow kinetically to larger nanocrystals, and we can interpret experiments based on our results for relatively small particles. It is experimentally observed that PVP in EG solution promotes the formation of {100}-faceted Ag nanocrystals, such as penta-twinned nanowires, ,,,,,, which can grow kinetically from decahedra ,, and cubes, ,,,, which can grow kinetically from FCC seeds. ,,, The predominance of decahedra, SCSF, and/or FCC nanocrystals in EG+PVP for most sizes in Figure is consistent with these experimental observations. On the other hand, Ag Ih are rarely synthesized in EG solution with PVP, and this is consistent with their relatively low fraction in Figure .…”
Section: Resultssupporting
confidence: 79%
“…Nevertheless, small nanocrystal seeds grow kinetically to larger nanocrystals, and we can interpret experiments based on our results for relatively small particles. It is experimentally observed that PVP in EG solution promotes the formation of {100}-faceted Ag nanocrystals, such as penta-twinned nanowires, ,,,,,, which can grow kinetically from decahedra ,, and cubes, ,,,, which can grow kinetically from FCC seeds. ,,, The predominance of decahedra, SCSF, and/or FCC nanocrystals in EG+PVP for most sizes in Figure is consistent with these experimental observations. On the other hand, Ag Ih are rarely synthesized in EG solution with PVP, and this is consistent with their relatively low fraction in Figure .…”
Section: Resultssupporting
confidence: 79%
“…When used as seeds, this opens the door to the controlled synthesis of a variety of AuNP products falling into either the O h - or D 5 h -symmetry class without the need for subsequent time-consuming and sample-specific purification steps because of the high purity of the starting material. While the present work has focused exclusively on AuNP pseudoisomers, pentatwinned nanoparticle morphologies have been observed for numerous systems including Ag, Pt, Pd, and Cu. , Thus, we anticipate that our approach would apply to a broad range of metals given the following conditions: (1) The shell must be capable of being selectively etched in the presence of the core, which is straightforward since shell metals are typically less noble than core metals to avoid galvanic replacement during heteroepitaxial growth. (2) The shell must deposit in a coherent manner to preserve the shape and strain properties of the core.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one class of models involves tracking the diffusive hopping of a single particle on a discrete array of lattice sites, possibly in the presence of trap sites . In a related application, MEQ have been applied to assess transit times of diffusing surface adatoms between facets during the growth of metallic NCs (where periphery sites of the target facet are designated as trap sites), thereby elucidating nontrivial faceted NC growth shapes. In our application, however, the discrete states of the system are entire configurations of the NCs (which might be regarded as elements of a high-dimensional space). In addition, the essential stochastic dynamics which must be assessed is not so much transitioning irreversibly into adsorbing trap states, but rather surmounting a “nucleation barrier”.…”
Section: Master Equation-based Analysismentioning
confidence: 99%